The Plant Blindness Profile of Secondary School Students - Wulandari, Selvi; Sunandar, Ari; Setiadi, Anandita Eka (Journal of Education Reseach and Evaluation, 2023)
Students' learning abilities, especially about plants, must be broader and more diverse. The lack of knowledge about the existence of plants in the environment so that they forget the role of the plants themselves for life. This study aims to analyze the percentage of plant blindness in secondary school students. The method used in the research is descriptive qualitative. In this study, data collection used questionnaires and interviews, data analysis was used to identify plant blindness in students in recognizing local vegetables by using statistical methods. The results showed that junior high school students had a higher rate of plant blindness than senior high school students. With a score range of ≥70%, junior high school students received 37.77% and senior high school students received 76.20%. Junior high school students with a score range of ≤70 were 62.23% and senior high school students were 23.8%, there is a considerable difference in value between the two value categories. In the future, students are expected to be more interested in knowing plants, especially local vegetables so that they can prevent plant blindness and can conserve local vegetables, besides that, teachers can make local vegetables a new learning resource for students.